Following Ezra : What One Father Learned About Gumby, Otters, Autism and Love From his Extraordinary Son - Fields-Meyer, Thomas (New York New American Library, 2011)
When his son Ezra was diagnosed with autism, Tom Fields-Meyer knew little about parenting and even less about neurological disorders. This intimate memoir chronicles his remarkable experiences of learning and growth from the time Ezra was diagnosed at age three to his bar mitzvah at thirteen. In that time, Ezra evolves from a remote, peculiar toddler to an extraordinary young man, not cured," but connected-in his own unique way-to the world around him
Keywords: Mental health -- Parents of autistic children -- United States